Opportunities and challenges in the sustainable integration of natural fibers and particles in friction materials for eco-friendly brake pads - Imran, Al Ichlas; Siregar, Januar Parlaungan; Mat Rejab, Mohd Ruzaimi; Cionita, Tezara; Hadi, Agung Efriyo; Jaafar, Jamiluddin; Fitriyana, Deni Fajar; Dewi, Rozanna (Mechanical Engineering for Society and Industry, 2024)
The high concentration of metallic components in the pad composite improves breaking ability at elevated temperatures and frequencies, bolstering the automobile's braking system. The brake pad operates through friction mechanisms, generating PM 10 and PM 2.5 particulate matter that is emitted into the atmosphere, adversely affecting the well-being of humans and animals. Therefore, eco-friendly materials like natural fiber and organic particles are being used as substitutes for the metal in brake pads. However, natural fibers and particles exhibit unique characteristics when interacting with other materials, presenting significant challenges in brake pad composites such as variations in physical properties, limited thermal resistance, and potential degradation at high temperatures and humid environments. These aspects play a crucial role and can affect the structural strength, wear resistance, and overall performance of composite brake pads, especially when operating under extreme braking conditions. This paper review critically discusses automotive braking systems, the benefits of non-natural fiber brake pads, the process of particle emission formation, the components and manufacturing factors of composite brake pads, and the environmentally friendly qualities of brake pads. This study provides an exciting opportunity to advance our knowledge of the presence of natural fibers and organic particles in composite brake pads, which greatly improves the performance of automotive brake systems because they have super physical and mechanical properties, as well as great tribological and thermal endurance. Moreover, eco-friendly brake pads are typically biodegradable, which helps reduce ecological damage, minimize health concerns for humans and animals, and promote a sustainable automobile sector. Furthermore, eco-friendly brake pads show great potential for further advancement in reducing pollutant emissions and enhancing performance.